Religion and National Identification in Europe: Comparing Muslim Youth in Belgium, England, Germany, the Netherlands, and Sweden - Fleischmann, Fenella (Journal of cross-cultural psychology, 2018)
How inclusive are European national identities of Muslim minorities and how can we explain cross-cultural variation in inclusiveness? To address these questions, we draw on large-scale school-based surveys of Muslim minority and non-Muslim majority and other minority youth in five European countries (Children of Immigrants Longitudinal Survey [CILS]; Belgium, England, Germany, the Netherlands, and Sweden). Our double comparison of national identification across groups and countries reveals that national identities are less strongly endorsed by all minorities compared with majority youth, but national identification is lowest among Muslims. This descriptive evidence resonates with public concerns about the insufficient inclusion of immigrant minorities in general, and Muslims in particular, in European national identities. In addition, significant country variation in group differences in identification suggest that some national identities are more inclusive of Muslims than others. Taking an intergroup relations approach to the inclusiveness of national identities for Muslims, we establish that beyond religious commitment, positive intergroup contact (majority friendship) plays a major role in explaining differences in national identification in multigroup multilevel mediation models, whereas experiences of discrimination in school do not contribute to this explanation. Our comparative findings thus establish contextual variation in the inclusiveness of intergroup relations and European national identities for Muslim minorities.